Beyond contradiction: The state and the market in contemporary Chinese water governance. Issue 108 (January 2020) - Jiang, Min; Webber, Michael; Barnett, Jon; Rogers, Sarah; Rutherfurd, Ian; Wang, Mark; Finlayson, Brian
Highlights: State control and marketisation in Chinese water governance are complementary rather than contradictory. China's water reform mirrors its overall economic reform taking an experimental approach. The state/market dichotomisation has little power to explain complexity of water governance. Attention to the 'both-and' hybridisation helps better understand the roles of state and market in water governance. Hybridisation of water governance takes diverse forms shaped by their particular political economies. Abstract: State/market interactions in water governance have long been interpreted in terms of the contradiction between water as a commons and water as a commodity. Recent challenges to this dichotomisation claim that it cannot provide a useful lens through which to interpret the complexity of water resources and their management. This paper provides evidence from China to show that a dichotomous interpretation of state/market interactions has little power to explain the formulation and evolution of water governance regimes. Through an analysis of China's water policy development over the 1998–2018 period, the paper outlines how state control and marketisation are complementary rather than contradictory, collectively contributing to a governance regime that serves broader political and economic goals as much as water management ones. We argue that better understanding of the roles of state and market in water governance requires moving beyond an 'either-or' point of departure, and paying greater attention to the 'both-and' hybridisation increasingly observed in water management.